Experts and designated users evaluations on visual tools screencast SketchUp Make (ViToS-SUM) - Faridah Hanim Yahya (Tanjung Malim, 2021)
Experts and designated users evaluations on visual tools screencast SketchUp Make (ViToS-SUM) by Faridah Hanim Yahya